Using Hello English to Improve Students’ Speaking Achievement at SMA Muhammadiyah Pagaralam - Fadilaturrahmah Fadilaturrahmah; Wice Oktaviani; Sri Wahyuni (JEIT (Journal of Educational Innovations and Technologies), 2025)
This research aims to determine whether or not Hello English can improve students speaking achievement. A quasi-experimental design of quantitative research was employed to conduct this research. The sample of this research consisted of 64 students from classes X IPS 1 and X IPS 3 at SMA Muhammadiyah Pagar Alam. Before the students used the Hello English application, the researcher gave a pre-test to the students to find out their prior knowledge. A post-test was given to all students to determine their achievement in speaking English. The t-test formula was used to analyze the collected data. Based on the findings of this research, the t-obtained value was 12.396, and the t-table value was 1.670. The result of this study showed that there were significant differences of students’ speaking achievement in experimental class after getting treatment from Hello English compared to students’ speaking achievement in control class (conventional method). Based on the result of statistical analysis the alternative hypothesis (hₐ), which stated that there was a significant difference in speaking achievement in teaching speaking by using Hello English to tenth graders at SMA Muhammadiyah Pagar Alam, was accepted. On the other hand, the null hypothesis (H₀) was rejected.